2016
DOI: 10.1002/anie.201605899
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Chemical Reactions and Organic Synthesis in Leidenfrost Droplets

Abstract: Leidenfrost levitated droplets can be used to accelerate chemical reactions in processes that appear similar to reaction acceleration in charged microdroplets produced by electrospray ionization. Reaction acceleration in Leidenfrost droplets is demonstrated for a base-catalyzed Claisen-Schmidt condensation, hydrazone formation from precharged and neutral ketones, and for the Katritzky pyrylium into pyridinium conversion under various reaction conditions. Comparisons with bulk reactions gave intermediate accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
101
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 26 publications
1
101
0
2
Order By: Relevance
“…[1] Confined volumes can take the form of sprays,g enerated by nebulization using electric and/ or magnetic fields,o rt hin films,g enerated for example by drop casting.F or instance,the Hantzsch reaction proceeds in 90 %y ield in charged microdroplets generated by electrospray. [5] Many other reactions involving C À H, [6] C À C, [2][3][4][5]7] C À N, [2,8] and CÀO [9] bond formation have been reported to be accelerated by factors of 10-10 6 in confined volumes. [5] Many other reactions involving C À H, [6] C À C, [2][3][4][5]7] C À N, [2,8] and CÀO [9] bond formation have been reported to be accelerated by factors of 10-10 6 in confined volumes.…”
mentioning
confidence: 99%
“…[1] Confined volumes can take the form of sprays,g enerated by nebulization using electric and/ or magnetic fields,o rt hin films,g enerated for example by drop casting.F or instance,the Hantzsch reaction proceeds in 90 %y ield in charged microdroplets generated by electrospray. [5] Many other reactions involving C À H, [6] C À C, [2][3][4][5]7] C À N, [2,8] and CÀO [9] bond formation have been reported to be accelerated by factors of 10-10 6 in confined volumes. [5] Many other reactions involving C À H, [6] C À C, [2][3][4][5]7] C À N, [2,8] and CÀO [9] bond formation have been reported to be accelerated by factors of 10-10 6 in confined volumes.…”
mentioning
confidence: 99%
“…[8] In almost all cases,anacceleration of several to several hundredfold has been noted relative to reactions conducted in organic solvents or even under neat conditions.M ellouli et al examined "on-water" cycloaddition reactions in biphasic microfluidic systems and investigated the role of surface-tovolume ratios on conversion rates,d emonstrating that acceleration can be ascribed to the increased rate of conversion at the surface. [11d] Additional studies have demonstrated that reactivity can also be enhanced at the surface of levitated droplets [13] and in microfluidic systems. Additionally,m any reactions conducted "on-water" allow for the facile isolation of products,w hich often precipitate and can be collected by simple filtration rather than after an often complex and time-consuming workup.…”
mentioning
confidence: 99%
“…Additionally,m any reactions conducted "on-water" allow for the facile isolation of products,w hich often precipitate and can be collected by simple filtration rather than after an often complex and time-consuming workup. [11d] Additional studies have demonstrated that reactivity can also be enhanced at the surface of levitated droplets [13] and in microfluidic systems. This unique reactivity in the ESI process was first proposed by Augusti et al [12] during their study of Eberlin transacetalization reactions in which acylium ions were generated by ESI of at etramethylurea solution and gaseous acetals were subsequently introduced and allowed to react with the acylium ions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently a movement towards tactic, functional and reactive droplets. This can be achieved by looking to nature for inspiration and many groups are reporting droplets which have biomimetic qualities, such as acting as vessels for chemical reactions [139], droplets with functional lipid bilayers [140,141], droplets which can mimic DNA transcription and translation [142] and even droplets which show self-reproduction [143].…”
Section: Solution Of Nacl and A Potential Difference Of 9 V Is Applmentioning
confidence: 99%